Unmet healthcare needs, health outcomes, and health inequalities among older people in China - Wu, Lili; Liu, Qin; Fu, Rao; Ma, Jia (Frontiers in Public Health, 2023)
Objective: Focusing on unmet healthcare needs among a large sample of Chinese older adults aged 60 and over, this study aimed to examine whether the experience of unmet healthcare needs was associated with adverse health outcomes, and how this association varied across needs which were related to health conditions. Study design: The 2013 wave of the China Health and Retirement Longitudinal Study was used. We adopted latent class analysis to identify groups based on health conditions. Then in each identified group, we examined the extent to which unmet needs were associated with self-rated health and depression. We also examined the impact of unmet needs due to various reasons to understand the channels by which unmet needs adversely affected health outcomes. Results: Compared to the mean, experiencing unmet outpatient needs were associated with 3.4% decrease of self-rated health, and people were twice as likely to have depression symptom (OR=2.06). Health problems were even more severe when experiencing unmet inpatient needs. The frailest people were most affected by affordability-related unmet needs, while quite healthy people were most affected by unmet needs due to availability. Conclusions: For tackling unmet needs, direct measures to particular populations are required in the future.